THE FINANCIALIZATION PROCESS AND ITS EFFECTS ON THE MEXICAN PRODUCTIVE SECTOR (1990-2016) - Lapa, Javier (International Journal of Management, Innovation & Entrepreneurial Research, 2018)
The process of economic financialization is defined as a stage of the capitalist system in which the profits obtained through financial channels acquire a growing importance, regarding to those related to production and distribution. The effects of this process are not limited to the financial sector, they also impact the productive one, at a macro and micro-economic level.In this sense, the Mexican Financial System (SFM) has gone through reforms arising from the adoption of a neoliberal growth model; according to which that financial liberalization contributes to the strengthening of both the financial and productive sector, creating a positive relationship among them. With the objective of evaluating, if this has materialized in the case of the Mexican economy,in this work is carried out; on one hand, a descriptive statistical analysis on the evolution of the financing granted to the productive sector; and on the other hand, an econometric analysis through a panel data model, relating to the plant investment; to identify the effects of such process, in the levels of productive reinvestment. That is, through the analysis of the two main links between the sectors involved, the implied risks of the process of financialization are showed, for a developing economy as the Mexican.